PERLINDUNGAN KONSUMEN TERHADAP KEBOCORAN DATA PRIBADI KONSUMEN PADA PLATFORM PERDAGANGAN ELEKTRONIK LOKAPASAR TOKOPEDIA (Analisis Putusan Nomor 235/Pdt.G/2020/PN.Jkt.Pst) - Amelia Farah Fadillah Rangkuti, (2023)
The emergence of the internet network that connects the world intends to facilitate the fulfillment of human activities and needs. The Constitution of the State of Indonesia, in Article 28G Paragraph (1) regulates the right to protection for oneself, family, honor, dignity, and property under its control. The right to privacy and personal data belonging to the public is an important part that must be protected so that people have a sense of security over their lives. Main Issues: (1) How Consumer Protection towards Consumer Personal Data Breached on Tokopedia E-Commerce Platform (Court Decision Analysis Number 235/Pdt.G/2020/PN.Jkt.Pst)?; (2) What are the efforts to protect consumers against cases of leakage of consumers' personal data on the Tokopedia marketplace electronic trading platform based on Court Decision Number 235/Pdt.G/2020/PN.Jkt.Pst? To answer these problems, a normative juridical research was carried out using secondary data as the main data related to and related to the research object which was then analyzed descriptively qualitatively. The conclusions of this research are (1) KKI as the plaintiff was not careful in determining which competency in carrying out the lawsuit in connection with the leakage of personal data of Tokopedia users, causing the lawsuit to be rejected; (2) Withdrawn from the entire series of incidents in the case of leakage of personal data of Tokopedia users/consumers, based on the Consumer Protection Act and related laws and regulations, efforts can be made through litigation in the form of lawsuits through competent courts and through non-litigation or outside court.